AB0092 Angiogenic and angiostatic mediators in spondyloarthritis. (23rd January 2014) - Riente, L.; Puxeddu, I.; Tronchetti, M.; Delle Sedie, A.; Bombardieri, S.; Migliorini, P.
Abstract : Background: The spondyloarthritis (SpA), including ankylosing spondylitis (AS) psoriatic arthritis, reactive arthritis, arthritis associated with inflammatory bowel disease and "undifferentiated" SpA (uSpA), are characterised by inflammatory back pain (IBP), sacroiliitis, peripheral arthritis, and enthesitis together with an association with HLA B27. Undifferentiated SpA is a diagnosis of exclusion, and can include patients with IBP who may have early ankylosing spondylitis but do not yet fulfil the classification criteria for AS. Angiogenesis, the formation of new capillaries from pre-existing vessels, isan early event in inflammatory joint diseases. Objectives: The aim of our study is to investigate the regulation of pro-angiogenic mediators and their endogenous inhibitors in uSpA and AS. Methods: Forty one adult patients with uSpA and 9 patients with definitive diagnosis of AS (according to the 1984 modified New York criteria) were studied. Vascular Endothelial Growth Factor (VEGF), Fibroblast Growth Factor (FGF-2) and their inhibitors Endostatin (ES) and Thrombospondin-1 (TSP-1) were measured in the sera of these patients and of 39 healthy subjects by enzyme immunoassays. Results: The serum levels of VEGF but not FGF-2 resulted significantly higher in the uSpA group than in the control subjects (P=0.0052). ES and TSP-1 were significantly higher in both uSpA (P<0.0001; P<0.0001, respectively) and AS (P=0.0014; P=0.0310, respectively) compared to the controls. Conclusions: Our results suggest that a disregulation of circulating angiogenic and angiostatic mediators takes place both in uSpA than in AS. Further investigations on angiogenic and angiostatic mediators in a larger number of patients with different subtypes of SpA would be useful to understand better their role in the pathophysiology of this group of disorders. Disclosure of Interest: None Declared